1994
DOI: 10.1111/j.1469-8137.1994.tb02952.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmolysis: new insights into an old process

Abstract: SUMMARY Early microscopists made detailed observations of the phenomenon of plasmolysis, many of which have passed into the historical record without comment. This review considers the significance of these observations in the light of recent cell‐biological studies which are addressing the complex relationships between the plasma membrane (PM) and the extracellular matrix, as well as the interrelationships of the PM, endomembrane system and cytoskeleton. Emphasis is placed on the relative roles of Hechtian st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 100 publications
8
124
2
Order By: Relevance
“…Interestingly, the yellow fluorescence appeared as a thin line circumventing the cells and coincided with the PM labeled by the CFP-tagged PM marker CFP-AtROP10 (Lavy and Yalovsky, 2006). After cell plasmolysis, YFP fluorescence resulted from the Tm-2 2 -MP interaction labeled the plasma membrane extensions (called Hechtian strands; Oparka, 1994) connecting the plasma membrane to the cell wall (Fig. 1C), also indicating the interaction occurred on the PM.…”
Section: Tm-2mentioning
confidence: 90%
“…Interestingly, the yellow fluorescence appeared as a thin line circumventing the cells and coincided with the PM labeled by the CFP-tagged PM marker CFP-AtROP10 (Lavy and Yalovsky, 2006). After cell plasmolysis, YFP fluorescence resulted from the Tm-2 2 -MP interaction labeled the plasma membrane extensions (called Hechtian strands; Oparka, 1994) connecting the plasma membrane to the cell wall (Fig. 1C), also indicating the interaction occurred on the PM.…”
Section: Tm-2mentioning
confidence: 90%
“…The work of Waymouth Reid (1890) showed that the plasma membrane in some places adhered to the cell wall and in others moved away from the cell wall during osmotic withdrawal of water from cells (reviewed in Kramer and Boyer, 1995). Much later, this was found to result from special structural features of the plasma membrane and cell wall called Hectian strands (Oparka, 1994). de Vries called this phenomenon plasmolysis, and it was then realized that the plasma membrane behaved as an active vital filter for specific solutes.…”
Section: It Must Be Osmosis!mentioning
confidence: 99%
“…The lack of wall-associated defence responses in compatible interactions with rust fungi is thought to involve an active suppression mechanism that is linked to a disruption of cell wall-plasma membrane connectivity (as indicated by a reduction in the frequency of Hecht threads beneath attempted penetration sites) [49 ]. Hecht threads are known to bridge the paramural space by physically connecting (unknown) sites in the cell wall and the plasma membrane [50]. The reduction in Hecht thread density appears to be a specific feature that is provoked by the rust fungus; the density of these threads was increased rather than decreased in both host and nonhost interactions with powdery mildews [49 ,51].…”
Section: Suppression Of Disease Resistance At the Cell Wallmentioning
confidence: 99%